Clinical experiments with the topical applications of dmso (dimethylsulfoxide) in some traumatic lesions of small and large animals - Nuri YAVRU; Erdoğan SAMSAR; Faruk AKIN (Eurasian Journal of Veterinary Sciences)
The aim of this study was to investigate the effectiveness of Dimethylsulfoxide (DMSO) in the treatment of some traumatic lesions occured in different parts of the body of small and large animals. For this purpose 9 ca ttle ( calf, heifer, co w, bull), 7 horses, 2 cocks, 1 ram, 16 dogs and cats, totally 35 animals were used as materials. Undiluted pure DMSO or its 1/3 diluted solutions of it with glycerine, were applied locally once or twice in a day for the period until recovery of the lesions. DMSO was poured on the surface of the traumatic lesions by naked hand or piece of cotton or gause. The lesions were recovered between 2 - 15 and 2 - 5 days in small and large animals respectively. The treatment was failed on only two animals. As a conclusion, DMSO applications were found to be a simple and effective treatment in acut traumatic lesions of both small and large animals.